Pengaruh LKS IPA Terpadu Tema Kesehatan Pencernaan Kita dalam Model Pembelajaran Kontekstual Adaptif Terhadap Kompetensi Siswa Kelas VIII SMPN 13 Padang - Renggina Anamunamita; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2018)
Students in the 21st century requires literacy skills in their learning and their daily live. The Indonesian government has supported the literacy of students through school literacy movement program. Besides that, the Indonesian government also has tried to improve the competence of students through integrated science teaching in Junior High School. The real condition shows that the result of learning outcome in science subject and literacy test of students can be classified into low category. An alternative solution to solve this problem is to apply the integrated science student worksheet in adaptive contextual teaching model. The purpose of this research is to investigate the effect of the application of Integrated science student worksheet on digestive health theme toward the competence of grade VIII students in SMPN 13 Padang. The type of research that used was quasi experiment with posttest-only nonequivalent control group design. Sampling technique in this research used purposive sampling. Instruments for collecting data consist of written test sheet of knowledge competency, observation sheet of attitude competency and performance assessment sheet of skill competency. Data from the research were analyzed by descriptive statistical analysis and compare two means test. Based on the data analysis can be stated that the application of Integrated science student worksheet on our digestive health theme has given significant effect toward competence of grade VIII students including knowledge, attitude and skill aspect of competences in SMPN 13 Padang at 95% confidence level.